Child Voice in Parenting Coordination: Toward a Model of Inclusion. (27th July 2020) - Yasenik, Lorri; Graham, Jonathan; Fieldstone, Linda
Abstract : Is it possible to bring the voice of children to the parenting coordination process without their involvement? And, if children are involved, what are the considerations for safe and appropriate inclusion? Ninety‐two parenting coordinators recently surveyed responded about their current practice and thoughts on child inclusion. Their comments, along with current trends in child‐inclusive practice, and with the Association of Family and Conciliation Courts Guidelines for Parenting Coordination (2019), assisted in providing a guiding framework and a forum for discussion for the community of parenting coordinators. Key Points for the Family Court Community: The AFCC Guidelines for Parenting Coordination provide some guidance regarding safe and meaningful child inclusion in parenting coordination. PCs should consider their professional background, training, skills, and experience before attempting to include children in the parenting coordination process; Child Consultants may be used in the role to bring the child's voice to parenting coordination if the PC's training and experience are not adequate to ensure the safety of the child in the process. Obtaining the child's voice is the most reliable way to bring the child's needs and preferences to the parenting coordination; otherwise coparents are mostly responsible for providing input, which puts the coparents in the position of accepting, dismissing or distorting their child's views. Parental conflict can be mediated by their child's voice. PCs must be able to modify what to bring back to parents so at any level of readiness parents may be more open to incorporating their children's thoughts and views into decision‐making.